A new genus and species of hypodermatine bot flies (Diptera: Oestridae). (16th December 2016) - PAPE, THOMAS; PIWCZYŃSKI, MARCIN; WYBORSKA, DOMINIKA; AKBARZADEH, KAMRAN; SZPILA, KRZYSZTOF
Abstract: The bot fly Gruninomyia mira Szpila & Pape, gen.n., sp.n. is described from Iran, North Khorasan, based on a single adult male and with no larval or host data. The monotypic genus shows a mixture of features otherwise found in either the rodent/lagomorph‐parasitizing oestromyine clade ( Oestroderma + Oestromyia ) or the artiodactyl‐parasitizing hypodermatine clade ( Hypoderma + Pallasiomyia + Pavlovskiata + Przhevalskiana + Strobiloestrus ) of subfamily Hypodermatinae. A morphology‐based phylogenetic analysis is marginally in favour of a position of Gruninomyia Szpila & Pape, gen.n. as sister taxon of ( Oestroderma + Oestromyia ). The COI barcode sequence is provided for the new species, and a phylogenetic analysis based on this marker for Oestridae retrieved from GenBank is in agreement with the conclusions based on morphological data. This published work has been registered in ZooBank:http://zoobank.org/urn:lsid:zoobank.org:pub:8F0CBE07‐4E74‐4186‐B690‐2C97D7ED7DA7 .